Understanding research in personal relationships : a text with readings - Dragon, William; Duck, Steve (SAGE, 2005)
This is a comprehensive introduction to the key readings on human and close relationships. Organized into twelve thematic chapters with editorial commentary throughout, the book offers a critical reading of the major research articles in the field of relationship studies published in the last few years.